2023
DOI: 10.1371/journal.pgen.1010575
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing analysis of canine urothelial carcinomas without BRAF V595E mutation: Short in-frame deletions in BRAF and MAP2K1 suggest alternative mechanisms for MAPK pathway disruption

Abstract: Molecular profiling studies have shown that 85% of canine urothelial carcinomas (UC) harbor an activating BRAF V595E mutation, which is orthologous to the V600E variant found in several human cancer subtypes. In dogs, this mutation provides both a powerful diagnostic marker and a potential therapeutic target; however, due to their relative infrequency, the remaining 15% of cases remain understudied at the molecular level. We performed whole exome sequencing analysis of 28 canine urine sediments exhibiting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…A cohort of humans with high-risk urothelial carcinoma, defined as a rate of 55% with a 2-year metastasis, had BRAF mutations on 25% of cases . A recent study found that dogs with urothelial carcinoma that are BRAF V595E undetected have other alterations within the MAPK pathway, including short in-frame deletions within BRAF exon 12 and MAPK1 exons 2 and 3 …”
Section: Review Criteriamentioning
confidence: 99%
“…A cohort of humans with high-risk urothelial carcinoma, defined as a rate of 55% with a 2-year metastasis, had BRAF mutations on 25% of cases . A recent study found that dogs with urothelial carcinoma that are BRAF V595E undetected have other alterations within the MAPK pathway, including short in-frame deletions within BRAF exon 12 and MAPK1 exons 2 and 3 …”
Section: Review Criteriamentioning
confidence: 99%
“…Standard pipelines are used for routine analyses such as mutation discovery with genomic sequencing reads (e.g., WGS or WES) and gene expression quantification with RNA-seq reads. [26][27][28] Typical pipelines include sequence quality control, alignment to the reference genome, mutation calling and annotation, and transcript/gene assembly and expression level quantification, with some of the commonly used software tools listed in Table 2. For sequence quality control, sequence reads are typically cleaned up with Trimmomatic, which removes adapter sequences and low-quality bases, and examined by FastQC.…”
Section: Standard Pipelinesmentioning
confidence: 99%
“…As with humans, there are multiple environmental factors that reportedly increase risk of canine iUC 18 . Approximately 80% of canine iUC tumors carry a somatic BRAF V595E mutation, which has been shown to increase activity of the MAPK signaling pathway 19 , 20 . Similarly, more than one third of human MIBC tumors carry activating mutations in the MAPK pathway 21 .…”
Section: Introductionmentioning
confidence: 99%